Breaking Up with Religion. The Experience of Deconversion from Catholicism to “No Religion” Among Polish Adolescents - Grupa, Michał (The international journal for the psychology of religion, 2026)
Based on qualitative research with 22 former Polish Catholic adolescents aged 14 to 19, this study takes a constructivist approach to understanding the process of leaving religion by examining deconversion narratives. Semi-structured interviews were conducted, and the data were analyzed using thematic analysis. The following six themes emerged: (1) avoiding peer exclusion as a pathway to deconversion (100%), (2) not seeing the value or practicality of religion (68%), (3) disillusionment with the religious leaders (77%), (4) freeing oneself from obligations (91%), (5) regaining space in life (82%), and (6) nothing terrible will happen if you go (77%). The results show deconversion as a process of social integration into the peer community, combined with a rejection of the constraints of religion, which appear incomprehensible to young people. Additionally, religious offerings are viewed as simplistic, and the functioning of religious institutions is seen as leaving much to be desired.